E-learning in Iraqi secondary schools / Reality and Challenges - Hayder Mohammed Muslim; Hani Abdulameer Ibrahim; Wasan Talib Hassan (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
This study aims to identify the trends and opinions of students and teachers towards the process of e-learning in an important period of human history, which is the period of the global crisis of the Corona pandemic and knowledge of its scientific term (Covid-19), as this period witnessed a complete closure of all aspects of social life, including operations. Educational in schools and universities in all countries of the world. During this period, electronic systems for education were employed to meet the procedures of imposing closures and social distancing, and this experience was new for most students, and therefore it was necessary to identify the general trends and opinions of students and teachers towards the electronic systems used in the education process. The study was applied to a sample of teachers and students of (50) teachers (250) students. The questionnaire was used as a tool to collect data after it was divided into several axes that included (20) questions that dealt with the positive and negative aspects of e-learning, and The results of the study showed the dissatisfaction with e-learning, and the majority of them tend to prefer the traditional learning system over e-learning. In the light of the results of the research, some conclusions were drawn and recommendations and suggestions.